Impact of punitive immigration policies, parent-child separation and child detention on the mental health and development of children - Laura C N Wood (BMJ Publishing Group, 2018)
In April 2018, the US government introduced a 'zero tolerance' illegal immigration control strategy at the US-Mexico border resulting in the detention of all adults awaiting federal prosecution for illegal entry and the subsequent removal of their children to separate child shelters across the USA. By June 2018, over 2300 immigrant children, including infants, had been separated from their parents for immigration purposes. Media reports and scenes of distraught families ignited global condemnation of US immigration policy and fresh criticism of immigration detention practices.Detention of children for immigration purposes is known to be practised in over 100 countries worldwide, despite a significant body of research demonstrating the extensive harm of such policies. This review explores and contextualises the key potential impacts of family separation and detention of children for immigration purposes including damaged attachment relationships, traumatisation, toxic stress and wider detrimental impacts on immigrant communities. As such, it is critical for host nation governments to cease the practice of family separation and child detention for immigration control and promote postmigration policies that protect children from further harm, promote resilience and enable recovery.